A memória dos esquecidos: narrativas dos sujeitos partícipes das ações do Mobral Cultural no Sertão de Alagoas - Silva, Jailson Costa da (2018)
This work was recorded as actions developed by the Programa Mobral Cultural, implemented by Movimento Brasileiro de Alfabetização (Mobral), in the municipality of Santana do Ipanema-AL (1973-1985). It aimed to understand - from the texture of stories and memories, how the subjects of the Alagoan backwoods experienced and re-signified the cultural actions developed by Mobral in a context of civil-military Dictatorship. It started from the following problematization: What were the contributions and resignifications experienced by the country person subjects, in the field of the cultural actions of the Mobral? It was based on the studies of: Certeau (2011a; 2011b; 2012), Lahire (2006; 2013), Bosi A. (1992), Brandão (2002a; 2002b) Fávero (1983), Freire (2011a; 2011b), among others. The interviews of the subjects involved were collected through interviews, through the qualitative approach of oral history, based on the theoretical postulates of Alberti (2008), Portelli (2010), Amado (1995b) and BosiE. (1994) privileging, also, the photography as source, using Cartier-Bresson (1971), Guran (2011), Leite (1993) and Mauad (1996). The oral and visual sources brought new reflections regarding the place - the Alagoan backwoods. What made me realize the contributions and resignifications that were possible in the context of the investigation, among them the appropriation of the local artists of the cultural actions developed in a Movement marked by the civil-military Dictatorship.